2021
DOI: 10.3390/cells10092494
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Fingerprint of Mecp2-Deficient Mouse Cortex: Evidence for a Pronounced Multi-Facetted Metabolic Component in Rett Syndrome

Abstract: Using unsupervised metabolomics, we defined the complex metabolic conditions in the cortex of a mouse model of Rett syndrome (RTT). RTT, which represents a cause of mental and cognitive disabilities in females, results in profound cognitive impairment with autistic features, motor disabilities, seizures, gastrointestinal problems, and cardiorespiratory irregularities. Typical RTT originates from mutations in the X-chromosomal methyl-CpG-binding-protein-2 (Mecp2) gene, which encodes a transcriptional modulator.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 110 publications
(149 reference statements)
0
20
2
Order By: Relevance
“…This treatment successfully improved the general phenotypic appearance of Mecp2 −/ y mice, as it stimulated their gain of weight, their growth, and their BMI. Hence, a beneficial impact on the distorted metabolic conditions in RTT [ 60 , 61 ] can be assumed. This indicates that the administered AOs did not only affect the central nervous system but also modulated the functions of peripheral organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment successfully improved the general phenotypic appearance of Mecp2 −/ y mice, as it stimulated their gain of weight, their growth, and their BMI. Hence, a beneficial impact on the distorted metabolic conditions in RTT [ 60 , 61 ] can be assumed. This indicates that the administered AOs did not only affect the central nervous system but also modulated the functions of peripheral organs.…”
Section: Discussionmentioning
confidence: 99%
“…Blood glucose levels were significantly reduced in Mecp2 −/ y mice, which may have been due to the intensified carbohydrate metabolism detected in our recent metabolomics study on Mecp2 −/ y cortex [ 61 ]. An amelioration of blood glucose contents in Mecp2 −/ y mice was observed upon AO treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic fingerprinting results had detected elevated AMP and ADP levels. This may lead to an observed increase in AMPK-mediated activation of glycolysis and TCA [ 181 , 212 ]. Hence, it is believed that impaired function of MeCP2 can disturb the AMPK signaling pathway and that it results in several symptoms in RTT patients, including high blood glucose and insulin resistance.…”
Section: The Interplay Between Mecp2 and Brain Metabolismmentioning
confidence: 99%
“…The study showcased that 101 metabolites that are involved in multiple metabolic pathways, including energy metabolism, lipid metabolism, amino acid metabolism, nucleotide metabolism and micronutrient metabolism, were significantly dysregulated. The researchers suggested that these dysregulated metabolites could become potential biomarkers for RTT, as clinical symptoms progressed [ 212 ]. Another study also indicated the abnormal transcript levels of HMG-CoA reductase, squalene epoxidase, and lanosterol synthase in the liver of Mecp2 null male mice at the age of 8 weeks.…”
Section: The Interplay Between Mecp2 and Brain Metabolismmentioning
confidence: 99%
“…Alterations in amino acid and carbohydrate metabolism have recently been confirmed in the cortex of severely symptomatic male MeCP2 KO mice [52]. Nonetheless, in the case of MeCP2-targeted gene expression profiling carried out since early development [53,54] and/or in different tissues [55] might be fundamental in distinguishing between geneticdriven primary defects and secondary features provoked by the accumulation of damages.…”
Section: Methylation Reading and Rett Syndromementioning
confidence: 99%